CLIMATE CHANGE MITIGATION DISCLOSURE IN ASEAN ENERGY INDUSTRY: DOES OWNERSHIP STRUCTURE HAS AN IMPACT? English - Octavio, Muhammad Fadhly Rizky; Wicaksono, Aditya Pandu (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of ownership structure (blockholder, domestic, government, foreign, and institutional) on climate change disclosure in the energy sector in Southeast Asia, filling the research gap on disclosure practices in sectors with high environmental impacts in developing countries. Using a quantitative approach, this study analyses data from 113 energy companies in six ASEAN countries (2017-2021) through panel data regression with the TCFD index as a disclosure measure. The results show that domestic and government ownership have a significant positive effect on climate change disclosure, while institutional ownership has a significant negative effect. Blockholder and foreign ownership do not show a significant effect. This study extends stakeholder theory by providing empirical evidence on the role of ownership structure in shaping environmental disclosure practices in developing countries, particularly in the energy sector.